Social Problems In The Story “Dry September” By William Faulkner - Sadullaev Feruz Bakhtiyorovich; Fayzullaeva Aziza Ibodullaevna (Euro Asian Journal Publishing, 2024)
William Faulkner, as one of the leading representatives of modern American literature of the 20th century, made an incomparable contribution to the development of prose work. Not only in the author’s novels and short novels, but also in small prose samples, a large place is devoted to the description of the social problems of that time, racism and interracial relations. The work “Dry September” is included in the collection of stories “These 13” and shows the originality of the writer’s modernist style. The analysis of the relationships of the characters described in the story clearly expresses the problems that exist between XX century US society and individuals, and ideas are explained using excerpts from the work.
Keywords: William Faulkner; Dry September; These 13; short story